Responding to Sexual Assault on Campus: A National Assessment and Systematic Classification of the Scope and Challenges for Investigation and Adjudication, (United States), 2014-2019 - Williams, Linda M. ([Verlag nicht ermittelbar], 2020)
This study, Responding to Sexual Assault on Campus: A National Assessment and Systematic Classification of the Scope and Challenges for Investigation and Adjudication, documents the current landscape (the breadth and differences) of campus approaches to investigations and adjudication of sexual assault. Data were gathered from a national sample of 969 colleges and universities in conjunction with interviews with key informants in 47 universities. Informed by a victim-centered focus, researchers developed a typology/matrix of approaches based on documented features of Institutes of Higher Education (IHE) policies related to sexual assault. In addition to the typology/matrix development, interviews and surveys of campus stakeholders and key informants were conducted to identify implementation strategies and challenges associated with each type of response model. The project ultimately produced guidelines that may assist colleges with assessing their capacity and preparedness to meet new and existing demands for sexual assault response models.